Use of recycled fine aggregate in concretes with durable requirements - Zega, Claudio Javier (2011)
The use of construction waste materials as aggregates for concrete production is highly attractive compared to the use of non-renewable natural resources, promoting environmental protection and allowing the development of a new raw material. Several countries have recommendations for the use of recycled coarse aggregate in structural concrete, whereas the use of the fine fraction is limited because it may produce significant changes in some properties of concrete. However, during the last decade the use of recycled fine aggregates (RFA) has achieved a great international interest, mainly because of economic implications related to the shortage of natural sands suitable for the production of concrete, besides to allow an integral use of this type of waste. In this study, the durable behaviour of structural concretes made with different percentage of RFA (0%, 20%, and 30%) is evaluated. Different properties related to the durability of concretes such as absorption, sorptivity, water penetration under pressure, and carbonation are determined. In addition, the results of compressive strength, static modulus of elasticity and drying shrinkage are presented. The obtained results indicate that the recycled concretes have a suitable resistant and durable behaviour, according to the limits indicated by different international codes for structural concrete.